2015/16 I-MOVE/I-MOVE+ multicentre case control study in Europe: moderate vaccine effectiveness estimates against influenza A(H1N1)pdm09 and low estimates against lineage mismatched influenza B among children - Kissling, Esther (2018)
Background:During the 2015/16 influenza season in Europe, the co-circulating influenza viruses were A(H1N1)pdm09 and B/Victoria, which was antigenically distinct from the B/Yamagata component in the trivalent influenza vaccine. Methods:We used the test negative design in a multicentre case–control study in twelve European countries to measure 2015/16 influenza vaccine effectiveness (VE) against medically-attended influenza-like illness (ILI) laboratory-confirmed as influenza. General practitioners swabbed a systematic sample of consulting ILI patients ainfluenza Vaccinend a random sample of influenza positive swabs were sequenced. We calculated adjusted VE against influenza A(H1N1)pdm09, A(H1N1)pdm09 genetic group 6B.1 and influenza B overall and by age group. Results: We included 11,430 ILI patients, of which 2272 were influenza A(H1N1)pdm09 and 2901 were influenza B cases. Overall VE against influenza A(H1N1)pdm09 was 32.9% (95% CI: 15.5-46.7). Among those aged 0–14, 15–64 and ≥65  years VE against A(H1N1)pdm09 was 31.9% (95% CI: -32.3-65.0), 41.4% (95%CI: 20.5-56.7) and 13.2% (95% CI: -38.0-45.3) respectively. Overall VE against influenza A(H1N1)pdm09 genetic group 6B.1 was 32.8% (95%CI: -4.1-56.7). Among those aged 0–14, 15–64 and ≥65 years VE against influenza B was -47.6% (95%CI: -124.9-3.1), 27.3% (95%CI: -4.6-49.4), and 9.3% (95%CI: -44.1-42.9) respectively. Conclusions: VE against influenza A(H1N1)pdm09 and its genetic group 6B.1 was moderate in children and adults, and low among individuals ≥65  years. VE against influenza B was low and heterogeneous among age groups. More information on effects of previous vaccination and previous infection are needed to understand the VE results against influenza B in the context of a mismatched vaccine.